Effects of whole body vibration training in patients with severe chronic obstructive pulmonary disease. Issue 6 (25th July 2013) - Pleguezuelos, Eulogio; Pérez, Maria Engracia; Guirao, Lluis; Samitier, Beatriz; Costea, Maria; Ortega, Pilar; González, Maria Victoria; Del Carmen, Virgilio Amin.; Ovejero, Laura; Moreno, Eva; Miravitlles, Marc
Abstract: Background and objective: To determine if whole body vibration training (WBVT) improves muscular force and modifies functional capacity parameters in patients with severe chronic obstructive pulmonary disease (COPD). Methods: We performed a randomized controlled trial in the outpatient Physical Medicine and Rehabilitation Department of a general hospital. Sixty stable male patients with COPD and mean forced expiratory volume in 1 s (FEV1) 34.3% (predicted) were enrolled with 51 patients completing the study. Participants were randomized into two groups: Whole Body Vibration Training Group (WBVTG), ( n = 26) undergoing three sessions per week for a total of 6 weeks and a Control Group (CG) ( n = 25) without intervention. The main outcome measures were isokinetic knee flexor and extensor testing in a concentric–concentric regime and exercise capacity measured by the 6‐min walking test (6MWT). Secondary outcomes were pulmonary muscular assessment with maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP). Results: No significant differences were observed between groups in maximum moment of isokinetic knee flexor/extensor testing force in a concentric‐concentric regime. In contrast, WBVTG patients showed a significant increase in the 6MWT (81.2 ± 9.2) meters; mean ± SD; P < 0.001). There was also a significant decrease in maximum oxygen desaturation in the 6MWT after 6 weeks of training (3.1 ± 1.1; P = 0.01). There were significant differences between groups in MIP and MEP at the end of the study in favour of the WBVTG. Conclusions: WBVT provided significant improvements in functional capacity in severe COPD patients without changes in muscular force. Abstract : This study shows that low frequency whole body vibration training provides significant improvements in functional capacity, measured by the 6‐min walking test, in severe COPD without changes in isokinetic knee flexor and extensor testing muscular force.